Harmful algal blooms: a Malaysian scenario - Mohammad Noor, Normawaty; Adam, Aimimuliani; Ahmad, Zuhairi; Saad, Shahbudin; Muhamad Bunnori, Noraslinda (2019)
Harmful Algal Blooms (HABs) are worldwide problems. It is defined as proliferation of algae under certain environmental condition. The algae produce toxin that can be transmitted to human through many different ways. This leads to a lot of negative impacts to human health including mortalities. However, some do not produce toxin but the high cell numbers killed farmed fish by anoxic condition. In Malaysia, HABs have occurred more than a decade ago and till today the problem still exist particularly in Sabah coastal waters. In Peninsular Malaysia, HABs problem is more sporadic. Several HABs species have been identified as causative species i.e. Pyrodinium bahamensa var. compresssum, Cochlodinium polykrikoides, Alexandrium tamiyavanichii and A. minutum. As a result, loss amounting to thousands of Ringgit Malaysia was reported besides human illness. Furthermore, the event brings negative sentiments on seafood among consumers and caused decreasing in market value. Therefore, the objectives of the paper are to share experience on HAB problems in Malaysia particularly in Kuantan Port, Pahang and Sabah coastal waters and suggest ways to address the problems. The new development of WebApps is among the potential ways to minimize the impact on public and fisheries industry.